2016
DOI: 10.1371/journal.pone.0167410
|View full text |Cite
|
Sign up to set email alerts
|

Kluyveromyces marxianus and Saccharomyces boulardii Induce Distinct Levels of Dendritic Cell Cytokine Secretion and Significantly Different T Cell Responses In Vitro

Abstract: Interactions between members of the intestinal microbiota and the mucosal immune system can significantly impact human health, and in this context, fungi and food-related yeasts are known to influence intestinal inflammation through direct interactions with specialized immune cells in vivo. The aim of the present study was to characterize the immune modulating properties of the food-related yeast Kluyveromyces marxianus in terms of adaptive immune responses indicating inflammation versus tolerance and to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…Thus, considering the potential of this genus for industrial phytase production, the fungus A. zeae B was selected for further evaluations. The yeast K. marxianus also presents good performance for large scale fermentations 22 and the production of various compounds, such as bioethanol 23,24 , β-galactosidase 25,26 and probiotics 27,28 . Therefore, it was selected as a model strain for phytase production.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, considering the potential of this genus for industrial phytase production, the fungus A. zeae B was selected for further evaluations. The yeast K. marxianus also presents good performance for large scale fermentations 22 and the production of various compounds, such as bioethanol 23,24 , β-galactosidase 25,26 and probiotics 27,28 . Therefore, it was selected as a model strain for phytase production.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it increases the production of the short-chain fatty acids acetate and propionate (Maccaferri et al, 2012). Kluyveromyces marxianus also modulates human dendritic cell function in vitro and induces a response dominated by Foxp3+ T regulatory lymphocytes (Smith et al, 2016). Such a response may bear positive consequences in those conditions characterized by excessive inflammation or uncontrolled proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of Foxp3 and IL-10 in Treg also increased [74]. In addition, research showed that after Kluyveromyces marxianus (a fungus that provides beneficial effects like probiotics) stimulated PBMCs, they found DC secreted more IL-12, IL-1, IL-6, and IL-10, which promoted the polarization of naive T cells to Treg [75].…”
Section: Immunomodulatory Effects and Mechanisms Of Probiotics Andmentioning
confidence: 99%
“…Finally, they cultured K. marxianus and S. boulardii with the DC-naive T cell cocultured system; they found that K. marxianus induced the differentiation of naive T cells to Foxp3+ Treg, increased secretion of IL-10, and controlled inflammation. Moreover, S. boulardii could induce differentiation of naive T cells to Th1, resulting in an increased secretion of IFN- γ [75]. Thomas et al cocultured bone marrow-derived DCs from Crohn's disease (CD) and ulcerative colitis (UC) patients with S. boulardii ; they found that DCs secreted less TNF- α but more IL-6 and IL-8 [86].…”
Section: Immunomodulatory Effects and Mechanisms Of Probiotics Andmentioning
confidence: 99%